2016
DOI: 10.1002/adma.201506119
|View full text |Cite
|
Sign up to set email alerts
|

Protein‐Nanoreactor‐Assisted Synthesis of Semiconductor Nanocrystals for Efficient Cancer Theranostics

Abstract: Transition metal sulfide nanocrystals are developed as a theranostic platform through the protein-nanoreactor approach with facile functionalization for multimodal NIRF/PA/SPECT/CT imaging and photothermal tumor ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
142
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(142 citation statements)
references
References 50 publications
0
142
0
Order By: Relevance
“…Recently, BSA was used as a nanoreactor to prepare theranostic agents. 22 This improved biological compatibility and controlled size. These agents achieved more efficient cancer-detection rates and better treatments in vivo.…”
Section: +mentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, BSA was used as a nanoreactor to prepare theranostic agents. 22 This improved biological compatibility and controlled size. These agents achieved more efficient cancer-detection rates and better treatments in vivo.…”
Section: +mentioning
confidence: 97%
“…22 Research has shown a significant difference between the functions of HSA and BSA. 23 The high homology and low cost of BSA makes it an appropriate research proxy for HSA.…”
Section: +mentioning
confidence: 99%
“…For example, Chen and co‐workers prepared a series of metal sulfide NPs by using proteins as a nanoreactor, where metal salts and sulfur resource (Na 2 S) were introduced to prepare protein encapsulated metal sulfide NPs. The metal sulfide NPs demonstrated an excellent platform for cancer therapy . Similarly, size‐controlled and biocompatible Ag 2 S NPs were developed as a second near‐infrared imaging agent for cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of drug delivery systems have been developed to realize combination chemotherapy and photothermal ablation. For instance, chemical drugs were directly loaded in photothermal nanoparticles, such as gold,19, 20, 21, 22 sulfide,23, 24, 25, 26 graphene and graphene‐like materials,27, 28, 29, 30 Prussian blue;31, 32 or loaded in mesoporous silica, smart polymer, aptamer, and cleavable linkages etc. modified on the photothermal particles 33, 34.…”
Section: Introductionmentioning
confidence: 99%